Effect of bioturbation on petrophysical properties: Insights from geostatistical and flow simulation modeling. (June 2019) - Eltom, Hassan A.; Rankey, Eugene C.; Hasiotis, Stephen T.; Barati, Reza
Abstract: As observed in many outcrops and cores, Thalassinoides burrow networks (TBN) within Glossifungites surfaces can be important for permeability enhancement, because the coarse-sediment infill provides permeable pathways in otherwise less permeable media. To explore the effect of bioturbation on reservoir quality, this study uses geostatistical models and fluid-flow-simulation models of TBN and burrow medium (matrix) of hypothetical TBN-bearing strata. Analysis of these models reveals a well-connected burrow network can occur in strata of as little as 12% burrow intensity, and burrow connectivity increases nonlinearly with increases in burrow intensity. Numerical flow simulations of TBN models indicate that gas production cumulative (GPC) is controlled primarily by TBN connectivity and matrix permeability. With an impermeable matrix, production comes through TBN (50 mD average permeability), starts only at burrow intensity of 30%, and GPC increases linearly with burrow intensity. With a permeable matrix (5 mD average permeability), and low permeability contrast between matrix and TBN (one order of magnitude) production starts at relatively low TBN intensity (4%), and GPC increases nonlinearly with burrow intensity. The interaction between matrix and TBN seems to connect more isolated TBN bodies, and increase GPC, and likely help the gas diffusion from matrix through TBN. The fluid flow simulation also illustrates the likelihood of the presence of permeability that drives early water breakthrough (super k) at burrow intensity > 50%. The results advance quantitative understanding of the impact of burrow connectivity on fluid flow properties of TBN-bearing strata and provide a workflow that can be used to model other burrow morphologies to understand their impact on flow properties of bioturbated reservoirs.